Onomatope yang digunakan oleh Food blogger Jepang dalam Media Sosial Instagram - Ayu Roslia, Ni Putu; Purnawati, Ketut Widya; Rauh Artana, I Nyoman (Humanis; Vol 23 No 3 (2019), 2019)
The title of this research is “Onomatopoeia Used by Japanese Food Blogger on Social Media site Instagram”. This research focuses on the form, function and meaning contained in onomatopoeia used by Japanese food bloggers on Social Media site Instagram. The theories used in this study are The Onomatopoeia Theory by Toshiko and Hoshino (1995: vi), Theory of Grammatical Onomatopoeic Functions by Fukuda(2003) and Semantic Theory by Chaer (2009) The results obtained in this study are that of the 25 data discussed there were 21 pieces of onomatopoeia data of the type of gitaigo and 4 pieces of onomatopoeia data of type giongo. And not all the same onomatopoeia always have the same grammatical function. In general, onomatopoeia meaning will change when the position of onomatopoeia as an adverbial in the relative clause in the sentence is to explain the noun that follows it.